2003
DOI: 10.2214/ajr.180.1.1800271
|View full text |Cite
|
Sign up to set email alerts
|

Steatocystoma Multiplex: Mammographic and Sonographic Manifestations

Abstract: Steatocystoma multiplex is manifest by multiple clinically palpable skin-colored or yellow nodules scattered on the axillae and the anterior chest wall. Steatocystoma multiplex is included in the differential diagnoses of lipoma, fat necrosis, galactocele, epidermal cyst, and so on, so radiologists need to be aware of its distinguishing features. The findings of a well-circumscribed round fat-density nodule on mammography or an intradermal hypoechoic nodule on sonography, combined with a family history of stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
12
2
Order By: Relevance
“…To our knowledge, steatocystoma multiplex, a rare autosomal dominant disorder in which numerous steatocystomas, pathologically resembling sebaceous cysts, develop in the skin of the anterior chest and axilla, has not been reported at breast MR imaging. However, it could conceivably manifest as multiple bilateral sebaceous cysts (40).…”
Section: Epithelial Cystsmentioning
confidence: 99%
“…To our knowledge, steatocystoma multiplex, a rare autosomal dominant disorder in which numerous steatocystomas, pathologically resembling sebaceous cysts, develop in the skin of the anterior chest and axilla, has not been reported at breast MR imaging. However, it could conceivably manifest as multiple bilateral sebaceous cysts (40).…”
Section: Epithelial Cystsmentioning
confidence: 99%
“…Based on these findings, we diagnosed the tumor as SCS.Some case reports of SCM have been accompanied by the ultrasonographic findings. [3][4][5] Mester et al reported a case of SCM with sonographic examination. They stated the lesions were well defined and hypoechoic, and some of them contained fluid-debris levels (i.e.…”
mentioning
confidence: 99%
“…Fifteen of the lesions were hypoechoic and the others were isoechoic. 4 Wan et al described ultrasonic features of SMC associated with a 59-year-old woman. The patient had multiple small nodules on the chest wall, axillae and forearm.…”
mentioning
confidence: 99%
“…The finding of a well circumscribed, round, fat density nodule on mammography or an intradermal hypoechoic nodule on sonography, combined with a family history and an extensive bilateral spatial distribution of the nodules, confirm the diagnosis of steatocystoma multiplex [12].…”
Section: Discussionmentioning
confidence: 87%
“…A lumen which is partly present in a few areas of the cord, is filled with the cellular debris of the keratinocytes, corneocytes, sebocytes, or the trapped hairs [4]. In comparison, the trichilemmal cysts take their origin from the outer root sheath of the follicle, the epidermal cysts take their origin from the infundibulum and the vellus hair shafts take their origin from the infundibuloisthmic junction or the isthmus [12].…”
Section: Discussionmentioning
confidence: 99%